Correlates of Adoption of Package of Practices in Bt Cotton by the Farmers of Ranga Reddy District of Andhra Pradesh - Deepthi. V , Hema. B , Kiranmayi. K and Jyothi. V, (Indian Journal of Extension Education, 2014)
The study was taken up with the main objective to study the correlates of the adoption of the recommended package ofpractices in Bt cotton by the farmers of Ranga Reddy District of Andhra Pradesh and their profile characteristics. For thepurpose of study fifty (50) farmers growing Bt cotton were selected at random from Kethireddypalli village of Moinabadmandal of Ranga Reddy district of Andhra Pradesh. The data was collected during 2013 through structured interviewschedule. The independent variables studied included age, education, family type, land holding, farming experience,training, extension contact, sources of information, social participation, market orientation, economic orientation, riskorientation, input availability and labour availability for cultivation of Bt cotton. While the dependent variable studiedincluded 'adoption of package of practices in Bt cotton. The adoption showed positive and significant correlation withtraining, sources of information and input availability at 5 per cent level of significance. The dependent variable alsoshowed positive and significant correlation with labour availability at 1per cent level of significance.